ChemInform Abstract: Synthesis and Lipophilicity Evaluation of Some Novel Indole‐Containing Pseudopeptides. Issue 24 (2nd June 2014) - Alavijeh, Nahid S.; Ramezanpour, Sorour; Alavijeh, Mohammad S.; Balalaie, Saeed; Rominger, Frank; Misra, Anil; Bijanzadeh, Hamid Reza
Abstract Most of the new indole‐containing pseudopeptides (V), (VIII), and (X) possess the optimal range of lipophilicity for oral absorption, cell membrane penetration and blood‐brain barrier permeation.